(untitled) (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2019)
One of the methods for assessing the efficiency of the passenger transport system of suburban communication during the design stage of the route network and improving its operation is the simulation of its operation. This process can be performed using a mathematical simulation apparatus. The necessary prerequisites for solving the set tasks in general form are determined by the parameters of their preliminary description, territorial location of nodes, elements of the system in the considered market of transport services, between which links of various kinds are formed, requiring quantitative assessment of implementations in accordance with the put forward needs for transport services. Adequacy conditions establish methods and algorithm for solving problems of determining quantitative characteristics of optimal transport processes and connections. Their characteristics should take into account the standards of reliability, safety, expediency, efficiency, and other specific operating conditions of the systems. The use of the latter to evaluate the consequences of changes in the route network of passenger traffic is of considerable interest for the following reasons: at present, a sufficiently complete mathematical apparatus is developed that allows to carry out the necessary modification of existing models, and takes into account the specifics of a specific route network; the use of mathematical models does not require significant resources and makes it easy to put them into practice with the use of computers, which allows for repeated analysis in the process of designing and operating the network; mathematical models, in contrast to full-scale modeling, measurement and statistical analysis of the parameters of a real route network of passenger traffic (if the route network is already designed and is in operation), allow to draw conclusions about the trends of network development, which is important in the study of the transport system passenger service. The work proposes an improved method of forecasting the potential of transport services, which can be used in modeling the functioning of the passenger transport system. Key words: passenger transport system, commuter service, transport service area, route network, transport services market.